Exploring barriers to assessment of bereavement risk in palliative care: Perspectives of key stakeholders Psychosocial - Sealey, M.; O'Connor, Moira; Aoun, Samar; Breen, Lauren (2015)
Background: Palliative care standards advocate support for grieving caregivers, given that some bereaved people fail to integrate their loss, experience ongoing emotional suffering and adverse health outcomes. Research shows that bereavement support tends to be delivered on an ad hoc basis without formal assessment of risk or need. To align support with need, assessment of bereavement risk is necessary. The overall aim is to develop a bereavement risk assessment model, based on a three-tiered public health model, congruent with palliative care bereavement standards for use in palliative care in Western Australia. The specific aim of this phase of the study was to explore the perspectives of key stakeholders and to highlight issues in relation to the practice of bereavement risk assessment in palliative care. Methods: Action research, a cyclical process that involves working collaboratively with stakeholders, was considered as the best method to effect feasible change in practice. The nine participants were multidisciplinary health professionals from five palliative care services, and a bereaved former caregiver. Data were obtained from participants via three 90 min group meetings conducted over five weeks. An inductive thematic analysis approach was used to analyse data following each meeting until saturation was reached, and the research team was satisfied that the themes were congruent with research aims.Results: Existing measures were found unsuitable to assess bereavement risk in palliative care. Assessment following the patient's death presented substantial barriers, directing assessment to the pre-death period. Four themes were identified relating to issues in need of consideration to develop a risk assessment model. These were systems of care, encompassing logistics of contact with caregivers; gatekeeping; conflation between caregiver stress, burden and grief; and a way forward. Conclusions: These group discussions provide a data-driven explanation of the issues affecting bereavement risk assessment in palliative care settings. A number of barriers will need to be overcome before assessment can become routine practice. We recommend the development of a brief, pre-death caregiver self-report measure of bereavement risk that may empower caregivers, lead to early intervention, and allow staff to remain focused on patient care, reducing burden on staff and palliative care services.